Micro middle ages - Dutton, Paul Edward 1952- (The New Middle Ages Series, 2023)
Intro -- Contents -- List of Figures -- Preamble -- An Incident: The Strange Case of the Green Children -- 1 The Stories -- 2 Why the Children Were There -- 3 Why the Children Were Green -- A Name: Heloise, Philosophess and Prostitute -- 1 The Assault on Philosophy -- 1.1 Magistra Philosophia -- 2 The Dance of Masters and Prostitutes around Money -- 2.1 Masters and Money -- 2.2 Nameless Prostitutes -- 2.3 Prostitutes and Schoolmen -- 2.4 Thais -- 3 The Dance of Abelard and Heloise Around Money -- 3.1 Abelard and Money -- 3.2 Abelard and Women -- 3.3 After Castration -- 3.4 Multa Heloisae Nomina -- 3.5 Coda -- A Scene: Slipping Below the Surface of the Bayeux Tapestry -- 1 Seeing the Image -- 2 The Object -- 3 Patron -- 4 The Making -- 5 Display -- 6 Animals -- 7 Border Issues -- 8 Two Fables -- 9 Below the Line -- 10 Experiencing the BT -- 11 The Usual Reading -- 12 History of the Scene -- 13 The Paired Paired Fish -- 14 The Daisy-Chain of Creatures: The So-Called Centaur -- 15 The Three Creatures -- 16 The Little Man on His Back -- 17 The Six Eels -- 18 Zooming Out -- 19 An Elf-Given Doubt -- 20 Bayeux Tapestry, Lower Border 17: What It Is and What It Means to Say -- Backpacking through Microhistory: Thanks for 'Nothing' -- 1 Micro Gazing -- 2 Micro Sizing History -- 3 Terms of Engagement -- 4 Small Things, Large Limits -- 5 Clues to the Prehistory of Microhistory -- 6 Holmes and Doyle Afoot -- 7 Micro Medieval Studies -- 8 Thanks for 'Nothing' -- A Joke: The Tiny Revolution of Theodulf's 'Stolen Horse' -- 1 Two Scenarios -- 1.1 The More Daring: A Microbridge Too Far -- 1.2 The More Likely: The Bridling of an Equestrian World -- A Sentence: The Desert War of One Carolingian Monk -- 1 The Codex and Its Colophon -- 2 The Journey -- 3 Ellenhart the Scribe -- 4 Why a Colophon -- 5 Why the Desert Fathers -- 6 Home -- Ambles End in Tears -- Index.